2019
DOI: 10.7762/cnr.2019.8.2.148
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Muscle Strength with Different Measures of Obesity and Lipid Profiles in Men and Women: Results from RaNCD Cohort Study

Abstract: We aimed to examine associations between muscle strength and obesity and serum lipid profile in Ravansar Non-Communicable Disease (RaNCD) cohort study. This study was conducted on 6,455 subjects aged 35–65 years old from baseline data of RaNCD in Iran. The associations between grip strength and adiposity measurements were explored using linear regression with adjustment for age, height, smoking status, alcohol intake, social class, and prevalent disease. The mean of body mass index (BMI) and muscle strength wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 27 publications
4
27
0
Order By: Relevance
“…Our results demonstrate that women with low muscle mass had higher values in adiposity indices (BMI, BAI, WC, WHR, WHtR, CI and LAP) when compared to participants with adequate muscle mass. Our findings are in accordance with the current literature that has shown that obesity is not only related to adverse metabolic outcomes [ 33 35 ], but also negatively affects skeletal muscle [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results demonstrate that women with low muscle mass had higher values in adiposity indices (BMI, BAI, WC, WHR, WHtR, CI and LAP) when compared to participants with adequate muscle mass. Our findings are in accordance with the current literature that has shown that obesity is not only related to adverse metabolic outcomes [ 33 35 ], but also negatively affects skeletal muscle [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…The present study also found the inverse relationship of age with HGS in both men and women, regardless of adjustment for confounding factors. This study also showed that BMI and resistance exercise, two other important determinants of HGS [ 31 , 32 ], are independent factors positively correlated with HGS. Several studies investigating the effect of hydration on muscle strength were unable to completely rule out the effect of weight gain due to water intake.…”
Section: Discussionsupporting
confidence: 67%
“…Several previous studies have supported the association between HGS and BMI. Pasdar et al 25) reported significantly increased HGS with increasing BMI in both men and women, with a more significant relationship in men than in women. Keevil et al 26) also reported this sex difference, suggesting that it might originate from differences in adipokine levels between men and women.…”
Section: Discussionmentioning
confidence: 94%